CNV-association meta-analysis in 191,161 European adults reveals new loci associated with anthropometric traits - Aurélien Macé (Nature Portfolio, 2017)
Individual SNPs have small effects on anthropometric traits, yet the impact of CNVs has remained largely unknown. Here, Kutalik and co-workers perform a large-scale genome-wide meta-analysis of structural variation and find rare CNVs associated with height, weight and BMI with large effect sizes.